2019
DOI: 10.1128/iai.00442-19
|View full text |Cite
|
Sign up to set email alerts
|

Generality of Post-Antimicrobial Treatment Persistence of Borrelia burgdorferi Strains N40 and B31 in Genetically Susceptible and Resistant Mouse Strains

Abstract: A basic feature of infection caused by Borrelia burgdorferi, the etiological agent of Lyme borreliosis, is that persistent infection is the rule in its many hosts. The ability to persist and evade host immune clearance poses a challenge to effective antimicrobial treatment. A link between therapy failure and the presence of persister cells has started to emerge. There is growing experimental evidence that viable but noncultivable spirochetes persist following treatment with several different antimicrobial agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 139 publications
(166 reference statements)
2
16
0
Order By: Relevance
“…In a mouse study in which heat-killed B. burgdorferi was injected under the skin of mice, borrelial DNA became virtually undetectable after 8 h [64]; the same study showed that no B. burgdorferi genomic materials can be detected in the skin, ear, ankle, or heart tissues of mice receiving killed bacteria two and four weeks after injection. Furthermore, in a ceftriaxone-treated mouse model that investigated the persistence of non-cultivable B. burgdorferi by monitoring the pathogen DNA level for 12 months, the Borrelia DNA level initially cleared after ceftriaxone treatment but resurfaced after 12 months, suggesting persistent infection [17,23]. In another non-human primate study, viable B. burgdorferi were recovered by xenodiagnoses and in vivo cultures from both antibiotic-treated and untreated rhesus macaques infected with B. burgdorferi [20,21].…”
Section: Borrelia Dna Persists In the Long Termmentioning
confidence: 99%
See 1 more Smart Citation
“…In a mouse study in which heat-killed B. burgdorferi was injected under the skin of mice, borrelial DNA became virtually undetectable after 8 h [64]; the same study showed that no B. burgdorferi genomic materials can be detected in the skin, ear, ankle, or heart tissues of mice receiving killed bacteria two and four weeks after injection. Furthermore, in a ceftriaxone-treated mouse model that investigated the persistence of non-cultivable B. burgdorferi by monitoring the pathogen DNA level for 12 months, the Borrelia DNA level initially cleared after ceftriaxone treatment but resurfaced after 12 months, suggesting persistent infection [17,23]. In another non-human primate study, viable B. burgdorferi were recovered by xenodiagnoses and in vivo cultures from both antibiotic-treated and untreated rhesus macaques infected with B. burgdorferi [20,21].…”
Section: Borrelia Dna Persists In the Long Termmentioning
confidence: 99%
“…In vivo animal studies with immunocompetent mice, dog, and non-human primate models have identified a surviving, but not cultivatable form of B. burgdorferi that can withstand antibiotic treatment [16][17][18][19][20]. Recent studies on rhesus macaques and mice confirmed these observations by demonstrating a metabolically active, persistent B. burgdorferi post-treatment in antibiotic-treated animals [20][21][22][23][24]. There are also human studies providing clinical evidence that a chronic form of Lyme disease could be caused by a persistent spirochetal infection, which could explain the lingering symptoms [25][26][27][28].…”
Section: Introductionmentioning
confidence: 96%
“…The lower metabolic activity of RBs may aid in the survival of the bacteria during antibiotic treatments, though RBs could only withstand exposure to harsh environments for short spans of time [ 74 ]. B. burgdorferi may have additional strategies to evade antibiotic treatment, including antibiotic tolerance, although the mechanisms remain undefined [ 80 , 81 , 82 , 83 , 84 ].…”
Section: Innate Responsementioning
confidence: 99%
“…Studies utilizing animal models of infection (Elsner, Hastey, Olsen, & Baumgarth, 2015;Embers et al, 2017;Hodzic, Imai, Feng, & Barthold, 2014;Straubinger, 2000) support the hypothesis that the ongoing symptoms in patients with unresolved Lyme disease may be due to persistent infection. Some animal studies, including those using a nonhuman primate model, demonstrate that the persisting bacteria are active and induce host responses months after the initial infection and standard treatments (Greenmyer, Gaultney, Brissette, & Watt, 2018;Hodzic, Imai, & Escobar, 2019). However, the actual causes of these ongoing symptoms remain to be defined.…”
Section: Lyme Diseasementioning
confidence: 99%